Reviewing The Core Values of State Civil Apparatus in Indonesia: Perspectives on Islamic Multiculturalism - Istiani, Nurul; Susilo, Adib (International Tatho Academics, 2024)
The phenomenon of problem of state civil service performance in Indonesia is a serious concern for the government in overcoming it. In this context, the government through the Circular Letter of the State Civil Service Agency has formulated the Core Values of the State Civil Apparatus. Through a normative-philosophical approach, this qualitative study aims to identify the values of multicultural Islamic education in the Core Values of the State Civil Apparatus in Indonesia. The value of multicultural Islamic education formulated by Azyumardi Azra is used as a theory of analysis. This study found the dimensions of Islamic multicultural Islamic education values in the Core Values of the State Civil Apparatus, among others, the value of tasamuh in Core Values in the form of harmony, wasathiyah values in Core Values in the form of collaborative and accountable service-oriented values, humanity values in Core Values in the form of competent and adaptive values, and peace values in Core Values in the form of loyal values. The theoretical implications of the findings of this study confirm that multicultural Islamic values can be synergistic with ethical values in building.